2022
DOI: 10.3390/ijerph19063496
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Criterial Algorithm for the Efficient and Ergonomic Manual Assembly Process

Abstract: Industry 4.0 introduces smart solutions throughout the company’s supply chain, including manual assembly, where the goal is to ensure shorter work cycle time, increase productivity and quality, while minimizing costs. Following the principles of this paradigm, this paper proposes a digital transformation of the manual assembly process by implementing a multi-criterial algorithm (MCA) for adjusting and configuring a human-centered smart manual assembly workstation to ensure efficient and ergonomic performance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…On the topic of inclusion/consideration of individuality and diversity, current studies address the opportunities and challenges of digital transformation for specific groups of employees [ 126 , 127 , 128 ]. Under the headings of sustainable and ethical organization [ 22 , 129 , 130 ], a wide variety of recent studies present contents that we have identified under the criterion of human-centered use of technical innovations. On the criterion of demand for a clear responsibility for occupational safety and health, research points to the problem of unclear categorizations of employers, employees and self-employed with regard to, e.g., platform work [ 131 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the topic of inclusion/consideration of individuality and diversity, current studies address the opportunities and challenges of digital transformation for specific groups of employees [ 126 , 127 , 128 ]. Under the headings of sustainable and ethical organization [ 22 , 129 , 130 ], a wide variety of recent studies present contents that we have identified under the criterion of human-centered use of technical innovations. On the criterion of demand for a clear responsibility for occupational safety and health, research points to the problem of unclear categorizations of employers, employees and self-employed with regard to, e.g., platform work [ 131 ].…”
Section: Discussionmentioning
confidence: 99%
“…As aforemen-tioned in the introduction, one of the main premises of I4.0 is to make work contexts more customizable and interconnected through technology, with the focus being increasing productivity [68][69][70][71][72]. In this light, the study developed by Turk et al [55] focused on creating an ergonomically suitable workstation for each worker, which could increase the productivity and efficiency of a manual assembly process. The authors focused on enhancing physical health by including components that can be individually adapted, such as worktable height, lighting, assembly nest orientation, and even the grab container settings, according to the person's reach.…”
Section: The Labor Market Ismentioning
confidence: 99%
“…The main limitation of this study was that it was apparently not applied in a real work context as the actual context was not specified. The authors mention that participants were untrained with the random assembly processes distributed to them for the inclusion of various types of movements [55]. The inclusion of some systems that could reduce the workers' operational leeway also seem to be endorsed, such as the pick-by-light technology [55] (pp.…”
Section: The Labor Market Ismentioning
confidence: 99%
“…As result, most employers have implemented one or several preventive measures: rotation of tasks to reduce repetitive movements or physical strain, encouraging regular breaks for people in uncomfortable or static postures including prolonged sitting/provision of ergonomic equipment or equipment to help with lifting or moving, promoting healthy lifestyles (11). Newly developed Information Technology systems for ergonomics assessment help companies to evaluate how ergonomic their workstations are (12)(13)(14)(15)(16). At the same time, they enable qualification profiles to be drawn up for the assignment of physically impaired employees in line with their abilities and minding principles based also on the WHO International Classification of Functioning, Disability and Health (ICF) (17).…”
Section: Introductionmentioning
confidence: 99%